The outcome of ovulation induction between letrozole-metformin versus letrozole alone in PCOS women with clomiphene citrate resistance - Noraini Abdul Mulalek (Kulliyyah of Medicine, International Islamic University Malaysia, 2019)
A prospective interventional study to compare the follicular response between combination of letrozole and metformin with letrozole alone as ovarian stimulating agents among clomiphene citrate resistant PCOS women. The primary outcome measured were number and size of mature follicles as well as clinical pregnancy rate while adverse effects of medication and adverse pregnancy outcome would be the secondary outcome measured. Total of 45 clomiphene citrate resistance women enrolled in this study which involved of 108 ovarian cycles. These women were randomly assigned to letrozole and metformin group and letrozole group. They received 2.5mg letrozole on day 2 to day 6 of menses with addition of 1000mg metformin daily in the first group. If they do not ovulate, the doses were increases from 2.5 mg to 5 mg then to 7.5 mg in the subsequent cycles. Follicular tracking done as per schedule to look for the outcomes. Ovulation occurred in 90.6% clomiphene citrate resistance PCOS women treated with combination of letrozole and metformin compared to 73% in women treated with letrozole alone. Additional metformin gave a significant larger size of mature follicle 19.0 (± 2.33) mm compared to letrozole alone 17.9 (± 1.96) mm (p value 0.014). 65.4% overweight women required 5mg letrozole while 63.6% obese women required higher dose of letrozole (7.5 mg) to ovulate. Pregnancy rate doubled with additional of metformin in the treatment. This study concluded that additional of metformin to letrozole as ovulation induction in clomiphene citrate resistance PCOS women will improve the ovulation and clinical pregnancy rate. Despite on higher doses requirement with 5 mg to 7.5 mg, the letrozole still maintain its mono-ovulatory property with no detrimental effect on endometrium.